Strategizing Kulim Hi Tech Park to enhance its competitiveness as global investment destination / Zafir Annuar Ghazali ... [et al.] - Ghazali, Zafir Annuar; Yaakob, Emiliya Niza; Othman, Hamidah (2012)
The main purpose of this study is to analyze the current operation of Kulim Hi Tech Park (KHTP) and proposing strategic options on enhancing the park competitiveness in the global investment market. As the pioneer of high technology industrial park model in Malaysia, KHTP has become catalyst of economic growth to State of Kedah and Malaysia from the inflows of Foreign Direct Investment (FOi) since its establishment in 1996. However, the recent declining inflows of FDI and new high technology industrial parks established in Malaysia and other countries have threatened KHTP to be core competitors in global investment radar screen. A macro-environment analysis PEST and business process SWOT Analysis were used in this study to diagnose the issues in KHTP. Benchmarking technique and evidence of secondary data information were used in constructing the strategic options to enhance KHTP competitiveness as global investment destination.